Optimalisasi Prenatal Gentle Yoga dan Self Hypnosis dalam Meningkatkan Pengetahuan Ibu untuk Mengatasi Keluhan Selama Kehamilan Trimester III - Marlin, Diane; Astria, Niki; Rahmawati, Dwi; Kurniasari, Lidya (Universitas Baiturrahim, 2025)
Complaints during pregnancy will continue to increase as the gestational age increases, pregnant women admit that they want actions or care that can reduce or overcome complaints felt by pregnant women so as to improve the welfare of pregnant women, through antenatal care by optimizing prenatal gentle yoga and self hypnosis. The method used in the implementation of this activity Pre-experimental design with a one group pretest posttest design using one group of subjects then measurements were carried out before and after treatment through counseling and demonstration of prenatal gentle yoga and self hypnosis by certified instructors with a total of 15 pregnant women in the third trimester then measured the level of knowledge of mothers to overcome discomfort with prenatal gentle yoga and self hypnosis. The results of this community service activity showed an increase in the knowledge of pregnant women where before being given education in the form of health counseling in overcoming complaints and how to overcome discomfort in mothers during pregnancy, the majority of pregnant women had good knowledge of 26.7% and the results of the evaluation after the implementation of counseling, the majority of pregnant women had good knowledge of 73.3%, so there was an increase of 46.6%. The conclusion in this activity is that partners experienced an increase in knowledge in overcoming complaints and how to overcome discomfort with prenatal gentle yoga and self hypnosis.